Analysis of mexicanolide‐ and phragmalin‐type limonoids from Heynea trijuga using high‐performance liquid chromatography/electrospray tandem mass spectrometry. (24th April 2013) - Yang, Wei; Fang, Dong‐Mei; He, Hong‐Ping; Hao, Xiao‐Jiang; Wu, Zhi‐Jun; Zhang, Guo‐Lin
<x xml:space="preserve">Abstract</x> RATIONALE Limonoids, a class of tetranortriterpenoids, exhibit various biological effects, including acting as potent antifeedants and insect growth‐regulators against various pests. The analysis of phragmalin‐ and mexicanolide‐type limonoids by collision‐induced dissociation tandem mass spectrometry (CID‐MS/MS) has not been reported. METHODS A high‐performance liquid chromatography/electrospray ionization (HPLC/ESI)‐MS/MS method was developed to investigate the fragmentation patterns of [M+NH4]+ ions for nine reference phragmalin‐ and mexicanolide‐type limonoids. The method was also used in the identification of limonoid compounds in botanic extracts of Heynea trijuga. RESULTS The losses of side chains and the furan part were the major fragmentation patterns. However, there was variation in the relative abundances of product ions resulting from the same fragmentation pathways. A total of 89 phragmalin‐ and mexicanolide‐type limonoids in botanic extracts of Heynea trijuga were detected and 50 of these compounds were identified or tentatively characterized based on elemental constituents, fragmentation pathways, and the profile of the major product ions of reference compounds. In addition, the isomers could be tentatively distinguished. CONCLUSIONS An HPLC/ESI‐MS/MS method was developed and could be used to simultaneously identify and screen phragmalin‐ and mexicanolide‐type limonoids in botanic extracts of Heynea trijuga. Copyright © 2013 John Wiley & Sons, Ltd.